(untitled) (Research, Society and Development, 2022)
This study presents and investigates the experiences of the historiographical trajectory of the Amazônia Mission and, therefore, of the development of the AMAZONIA-1 Satellite in its 41 years. For this, a Systematic Mapping (SM) was carried out to track the state of the art of the Satellite whose result was obtained only 7 academic references. After that, the Document Analysis (DA) was carried out by collecting experiences and records of artifacts through the transcription of videos present on the Youtube Platform. In addition to obtaining official documents from INPE, in order to develop the evolution of the historical framework and the analysis of the main satellite technologies under stages of the mission life cycle. Indeed, a historical narrative was built to use, in addition to official historical sources, the gathering of historical, educational, economic and environmental observations, especially technological. It starts from the perspective of researchers, technologists, administrators, engineers and teams, participants and scholars of the Amazon mission. As a result, a hybrid AD methodology was also developed, which is anchored, both initially in the MS, and in the course of the work in the bibliographic research. It was also possible to foster the debate on satellite development, providing: i) important appointments educational, environmental and economic notes; ii) foundation of the conceptual-practical aspects of the space mission; iii) the formulation of the preliminary project definition and; iv) the Amazon Mission in its historical and factual experiences (2001-2021) of optimization, technology transfer, implementation and launch of the artifact.